Cisatracurium inhibits the growth and induces apoptosis of ovarian cancer cells by promoting lincRNA-p21. Issue 1 (1st January 2021) - Zhu, Dezhang; Shi, Caifeng; Jiang, Yanan; Zhu, Kongjuan; Wang, Xiangzhen; Feng, Wei
ABSTRACT: As a common muscle relaxant, cisatracurium has shown good antitumor effect on some tumors. Recent studies reported that cisatracurium could inhibit the progression of colon cancer by upregulating tumor suppressor gene p53. However, its role in ovarian cancer and its regulatory effect on p53 and p53 downstream targeting gene long intergenic noncoding RNA p21 (lincRNA-p21) is still unknown. Quantitative Real-time Polymerase Chain Reaction (qRT-PCR) was used to assess the expression of p53, lincRNA-p21 and miR-181b. Cell viability and proliferation were detected by CCK-8 assay and Edu staining, respectively. Wound-healing and Transwell assays were performed to determine the abilities of cell migration and invasion. Apoptosis was evaluated by TUNEL staining. Luciferase reporter assay was conducted to detect the relationship between lincRNA-p21 and miR-181b. As a result, cisatracurium could increase the expressions of p53 and lincRNA-p21 of ovarian cancer cell line (OVCAR-3) in a dose-dependent manner. In addition, cisatracurium significantly inhibited the proliferation, migration and invasion of OVACR-3 cells, and induced apoptosis. However, these above changes in biological function can be attenuated by lincRNA-p21 knockdown. Next, lincRNA-p21 could directly target miR-181b and negatively regulate its expression by luciferase reporter assay. In conclusion, cisatracurium inhibited the progression of OVCAR-3 cells through upregulation of lincRNA-p21 expression activated by p53 inhibiting miR-181b expression. The experimental results provide a new research idea for the application of cisatracurium in ovarian cancer.